Associations between physical activity, sedentary behavior, and urinary oxidized guanine in colorectal cancer patients: results from the ColoCare Study - Viskochil, Richard; Gigić, Biljana; Lin, Tengda; Skender, Stephanie; Böhm, Jürgen; Schrotz-King, Petra; Steindorf, Karen; Owen, Robert; Figueiredo, Jane C.; Li, Christopher I.; Siegel, Erin M.; Hardikar, Sheetal; et al. (Applied physiology, nutrition, and metabolism, 2020)
To determine associations between physical activity (PA), sedentary behavior (SB), and oxidative stress in colorectal cancer patients, ColoCare Study participants in Germany wore an accelerometer 6 and/or 12 months after surgery. Spearman partial correlations were used to assess associations between PA and urinary concentrations of oxidized guanine, a validated marker of oxidative stress. There were no significant associations between PA or SB and oxidized guanine in n = 76 measurements (ng/mg creatinine; r = 0.03, p = 0.76 for PA, r = -0.05, p = 0.69 for SB). Novelty Objectively measured PA was not associated with a marker of oxidative stress in colorectal cancer patients.